IRC augmented reality (IRC AP) - Suito, Helmi Iskandar; Dzolmi, M Helmi; Mohamad, Nik Mohd Hamidi; Zainoddin, M Aqil Zafry; Mahmud, Zaidah (Universiti Teknologi MARA, Kedah, 2019)
The emerging technological advancement in the computer has created numbers of interesting applications, one of which is augmented reality (AR). However, the libraries are still employing an outdated technology that heavily relies on human interaction. With the increasing number of library users observed in recent days, this trend will cause the flooding of enquiries at the circulation counter which in turn will jeopardize the quality of the library’s services delivered. IRC Augmented Reality (AR) project is introduced to minimize the dependency of the counter staff in answering the enquiries by employing an interactive and more engaging platform as a guide to the user. It is also aimed to empower the personalized services offered by IRC. AR in a simple definition is a layer of the computer-generated image that overlays the real-world environment which allows seamless integration between the virtual and real world. It has been revolutionized by technological advancements in various fields such as games and education. This IRC AR provides the patron information that would help them in determining the correct resources the fit their needs. Places like Shelves in ground level, User Advisor Desk, F1 simulator are equipped with AR capabilities where it helps user to give an extra information, in addition, it also provides buttons for another function through IBEST system for F1 simulator and appointment with a librarian. For self-check machine and circulation counter, IRC AR provide video tutorials to assist users in using the equipment. In conclusion, IRC AR is successfully deployed to the user where it is proven that this application can reduce the user’s dependency on the counter staff. It also improves the efficiency of the services offered by providing additional information for user to utilize IRC service and facilities